The Professional Performance of Media and Social Network During the Crisis: Audience’s Perception of Covid-19 Coverage - Bekhit, Elsayed; Al-Ali, Fawzia (Advances in Social Sciences Research Journal, 2023)
The study aimed to identify and analyze the public attitudes and perceptions of the treatment of the coronavirus crisis by media and communication organizations in the UAE. To what extent have they succeeded in introducing the CORONA virus and its symptoms, methods of prevention and precautionary measures, their perceptions of the most important means of communication that succeeded in raising their awareness of the crisis and affected their handling of the crisis, and their assessment of the nature of the information obtained from these mass media and social media in terms of its completeness, accuracy, etc. The study revealed a convergence in the roles that social media and the media have been interested in dealing with the virus and their relevance to the roles assigned to them, and both agreed to prioritize the roles related to the identification of THE CORONA virus, to raise awareness of the importance of taking precautionary measures with regard to HIV and to inform members of society about the symptoms of the virus. These results indicated that both the media and social media play an important role in spreading information related to the virus than in the roles of awareness and guidance. It also reveals that there is a lack of effort exerted by both media in the use of specialists to fulfil their roles in enhancing the awareness and guidance of the virus. The study also found that the public relied more on social media than the conventional media to obtain information about the coronavirus, which is risky because of the inaccuracy and reliability of the information published through social media. The public’s assessment of the professional performance of the conventional media was also more positive than their assessment of the professional performance of social media.